2016
DOI: 10.1080/00071668.2015.1098766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic supplementation and dietary fat sources on broiler performance, serum lipids, muscle fatty acid profile and meat quality

Abstract: A 42-d trial was conducted to investigate the effect of adding a synbiotic supplement to diets containing two different types of fat on performance, blood lipids and fatty acid (FA) composition and oxidative stability of breast and thigh meat in broilers. A total of 800 one-d-old male broiler chickens were randomly assigned into 1 of 8 treatments with 4 replicates of 25 birds per treatment. The experiment consisted of a 4 × 2 factorial arrangement of treatments including 4 concentrations of synbiotic (0, 0.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 49 publications
6
37
2
Order By: Relevance
“…Findings of a recent metaanalysis indicated that probiotics had a significantly good effect on normalizing total cholesterol, as we observed (27). Ghasemi findings also indicated that the addition of synbiotic to the diet decreased serum cholesterol and LDL cholesterol concentrations in broilers (28). In contrast with our results, Wong VW et al did not find any significant effect for Lepicol probiotic and prebiotic formula on body mass index, waist circumference, glucose, and lipid levels (29).…”
Section: Discussioncontrasting
confidence: 56%
“…Findings of a recent metaanalysis indicated that probiotics had a significantly good effect on normalizing total cholesterol, as we observed (27). Ghasemi findings also indicated that the addition of synbiotic to the diet decreased serum cholesterol and LDL cholesterol concentrations in broilers (28). In contrast with our results, Wong VW et al did not find any significant effect for Lepicol probiotic and prebiotic formula on body mass index, waist circumference, glucose, and lipid levels (29).…”
Section: Discussioncontrasting
confidence: 56%
“…Ghasemi et al . [45] observed a similar effect of improved FCE after administration of synbiotics in broiler chicken diets. In contrast, Murshed and Abudabos [46] reported poorer FCE in chickens fed diets with a synbiotic consisting of MOS, beta-glucans, and a highly active strain of Bacillus subtilis (DM17299).…”
Section: Discussionmentioning
confidence: 78%
“…Axling et al () also noticed that the supplementation of probiotic down‐regulates the mRNA expression of hepatic lipogenic enzyme in broilers, with a subsequent reduction in the liver lipogenesis. Conflicted with these findings, others reported that synbiotic supplements did not modify the serum triglyceride and VLDL levels (Ghasemi, Shivazad, Mirzapour‐Rezaei, & Karimi‐Torshizi, ). It is interesting to notice the decreased serum total protein and albumin in the OA‐supplemented group.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, Min, Yang, Xu, and Gao () reported that the broiler diets supplemented with a combination of B. subtilis and mannan‐Oligosaccharide reduced the plasma MDA level. The lowered MDA level may be related to the regulatory action of synbiotics on the FA profiles of broiler muscles (Ghasemi et al, ). Recently, Zhang et al () observed that the dietary supplementation of synbiotic decreased the 8‐OHdG level in broiler chicks at 21 day of feeding ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%